A pleasant familiar odor influences perceived stress and peripheral nervous system activity during normal aging - Joussain, Pauline; Rouby, Catherine; BENSAFI, Moustafa (Frontiers in Psychology, 2014)
Effects of smells on stress have been demonstrated in animals and humans, suggesting that inhaling certain odorants may counteract the negative effects of stress. Because stress plays a key role in cerebral aging, the present study set out to examine whether positive odor effects on perceived stress can be achieved in elderly individuals. To this end, two groups of aged individuals (n=36 women, aged from 55 to 65 years), were tested. The first group was exposed for 5 days to a pleasant and, by end of exposure, familiar odor (“exposure odor”), whereas the other was exposed to a non-scented control stimulus. Stress and mood states were assessed before and after the 5-day odor exposure period. Psychophysiological markers were also assessed at the end of exposure, in response to the “exposure odor” and to a “new odor”. Results revealed that stress on this second exposure was decreased and zygomatic EMG activity was increased specifically in the group previously exposed to the odor (p< 0.05). Taken as a whole, these findings offer a new look at the relationship between perceived stress, olfaction and normal aging, opening up new research perspectives on the effect of olfaction on quality of life and well-being in aged individuals.